Surface oxidation of petroleum pitch to improve mesopore ratio and specific surface area of activated carbon - Song Mi Lee (Nature Portfolio, 2021)
Abstract In this study, surface oxidation of petroleum pitch was performed to enhance the thermal stability, specific surface area, and mesopore ratio of activated carbon. The oxygen uptake of the pitch by surface oxidation has a strong influence on the formation of the specific surface area and pore size of activated carbon. It was confirmed that the oxygen uptake from the surface to the inner side of the surface oxidized pitch was the highest at the temperature of 330 °C (IP330-AC), with a mesopore ratio of 63.35% and specific surface area of 1811 m2 g−1. The oxygen content of the surface oxidized pitch increased proportionately with the mesopore ratio in activated carbon. The specific surface area and mesopore ratio of IP330-AC were respectively 163% and 487% higher than those of petroleum-based commercial activated carbon (A-BAC), and 102% and 491% higher than those of coconut-based commercial activated carbon (P60).